Navigating ChatGPT in EFL Academic Writing: Pre-Service Teachers’ Experiences, Concerns, and Pedagogical Reflections - Shelia Anjarani; Miftahul Furqon; Dodi Siraj Muamar Zain; Hera Septriana; Dwi Isnaeni (Universitas Hamzanwadi, 2026)
The growing presence of generative artificial intelligence in higher education has reshaped how academic writing is learned, practised, and taught. This study explores pre-service teachers’ experiences of using ChatGPT in academic writing and examines their pedagogical reflections on its possible integration into EFL writing instruction. While previous studies have widely discussed students’ use of ChatGPT as a writing assistant, limited attention has been given to pre-service teachers, who occupy a dual position as language learners and future educators. Using a narrative inquiry design, this study involved eight EFL pre-service teachers from a private university in Indonesia. Data were collected through semi-structured interviews and analyzed thematically. The findings show that ChatGPT supported participants in generating ideas, organizing texts, improving language accuracy, and increasing writing efficiency. However, participants also expressed concerns about factual inaccuracies, fabricated references, academic integrity, and over-reliance, which may weaken creativity, learner agency, and independent thinking. Importantly, the participants did not view these challenges merely as limitations, but reframed them as pedagogical opportunities. They proposed strategies such as combining AI-assisted and AI-free writing tasks, integrating fact-checking activities, comparing AI feedback with human feedback, and encouraging students to justify their use of AI-generated suggestions. These findings suggest that pre-service teachers are developing critical pedagogical reasoning in response to generative AI. The study highlights the need to integrate AI literacy into teacher education programs to promote ethical, reflective, and pedagogically informed uses of ChatGPT in EFL academic writing classrooms.